PRMT5 Maintains Homeostasis of the Intestinal Epithelium by Modulating Cell Proliferation and Survival - Leilei Li; Zhe Zhang; Xu Wang; Haiyong Zhao; Liansheng Liu; Yanhui Xiao; Shan Hua; Ye‐Guang Chen (Advanced Science)
Abstract Intestinal homeostasis is sustained by self‐renewal of intestinal stem cells, which continuously divide and produce proliferative transit‐amplifying (TA) and progenitor cells. Protein arginine methyltransferases 5 (PRMT5) plays a crucial role in regulating homeostasis of various mammalian tissues. However, its function in intestinal homeostasis remains elusive. In this study, conditional knockout of Prmt5 in the mouse intestinal epithelium leads to a reduction in stem cell population, suppression of cell proliferation, and increased cell apoptosis within the intestinal crypts, accompanied with shortened gut length, decreased mouse body weight, and eventual animal mortality. Additionally, Prmt5 deletion or its enzymatic inhibition in intestinal organoids in vitro also shows resembling cellular phenotypes. Methylome profiling identifies 90 potential Prmt5 substrates, which are involved in RNA‐related biological processes and cell division. Consistently, Prmt5 depletion in intestinal organoids leads to aberrant alternative splicing in a subset of genes related to the mitotic cell cycle. Furthermore, Prmt5 loss triggers p53‐mediated apoptosis in the intestinal epithelium. Collectively, the findings uncover an indispensable role of PRMT5 in promoting cell proliferation and survival, as well as maintaining stem cells in the gut epithelium.